If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -8 = 5x + -5y Reorder the terms: -8 + 6y = 5x + -5y Solving -8 + 6y = 5x + -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. -8 + 6y + 5y = 5x + -5y + 5y Combine like terms: 6y + 5y = 11y -8 + 11y = 5x + -5y + 5y Combine like terms: -5y + 5y = 0 -8 + 11y = 5x + 0 -8 + 11y = 5x Add '8' to each side of the equation. -8 + 8 + 11y = 8 + 5x Combine like terms: -8 + 8 = 0 0 + 11y = 8 + 5x 11y = 8 + 5x Divide each side by '11'. y = 0.7272727273 + 0.4545454545x Simplifying y = 0.7272727273 + 0.4545454545x
| y*dx+(x^2*y-x)*dy=0 | | ydx+(x^2*y-x)dy=0 | | v^2+44v-6600=0 | | 8sin^2(x)=4 | | 2ln(x)-2=0 | | 4xy+4x+4y+1=0 | | 44x-1=87 | | x+2/4=x+6/2 | | C=(-6x-2)(-3x-5) | | B=-4x(2x-5)+4x(6+3x) | | (x+22)(x+22)=0 | | v^2+44v-1000=0 | | A=(4x+3)-(7x+5) | | -2u+16=-4 | | 4x^3-4x-3=0 | | 5x+37=7x-9 | | 12-8x=116-36x | | 3(x+4)-x=5 | | 5(5x-5)-3=x-6-2 | | 2x^2+2x-119=0 | | -8x+3x-7= | | C+ax=b-dx | | 6x+3=-37+2x | | 9x+8=68+3x | | B=-1+3a | | 2(x-5)-3(2t-7)=12-5(3t+1) | | 30-8x=15-5x | | 2u+4=u-7 | | 5+4(3c-1)= | | 2(5x+2)=3x-17 | | 4(3x-4)+8=4x+32 | | 22=2(2x-1) |